The problem of scientific hypermedia discourse perception - L A Egorova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2009)
The article considers the role of the addressee in the development of scientific discourse. A particular attention is paid to the communicators interaction and the factors that the successful communication is based on.